Revisitando los orígenes del trabajo social: Richmond frente a Addams - Verde-Diego, Carmen (Miscelánea Comillas, 2022)
The historical and epistemological origins of social work have reached Spain from the United States. And they have done so in a biased way. Traditionally, literature has favored a certain way of understanding the profession and the discipline which stems from the Charity Organization Society (COS) and the case work which was eventually systematized by Mary Ellen Richmond. In this article, we analyze, after a bibliographical and documentary revision, the tradition inaugurated by Jane Addams in the USA, in the Hull House Settlement, where she developed community and group social work. We will consider the coincidences between Addams and Richmond, especially in their biographies, and their divergences, in particular in their way of envisaging social work.